SUBSTITUSI TEPUNG PISANG TERMODIFIKASI PADA PEMBUATAN KABOSOL TERHADAP KADAR GULA DARAH ORANG DEWASA - Firdaus Syafii; Yudianti Yudianti (Jurnal Kesehatan Manarang, 2019)
Appropriate treatment for people with diabetes mellitus (DM) is done by eating patterns to control blood glucose levels. The concept of the glycemic index (IG) is an approach to choose foods that are good in managing blood glucose levels. One of the local food ingredients that has the potential to be used as a substitute for flour and has a low GI is a banana. Modification of banana flour makes bananas have a lower glycemic index value that can control blood sugar levels. The purpose of this study was to determine the effect of modified banana flour substitution on the manufacture of kabosol on the value of an increase in adult blood sugar levels. The design of this study was carried out using a completely randomized design (CRD) using four modified banana four concentration variables (50%, 75%, 100%,) and 0% as a control. Based on the results of the study, there was a significant effect of modified banana flour on making kabosol on the value of an increase in blood sugar (p = 0.007). The lowest increase in blood sugar levels was obtained from respondents who consumed banana flour substitute kabosol with a concentration of 100%, which amounted to 3.1 mg / dL. Kabosol with 100% modified banana flour substitutes can be used as functional food because it can control blood glucose levels.